The Vanderbeekers on the road - Glaser, Karina Yan (Glaser, Karina Yan. Vanderbeekers, 2022)
In this new adventure in the New York Times bestselling series, the Vanderbeekers depart Harlem to celebrate their dad's birthday. But their surprise road trip turns rocky when the younger kids try to keep their family from ever facing change. Our beloved Harlem family is putting the VAN in Vanderbeekers as they hit the highway to give their dad the best birthday surprise EVER! Re-creating a road trip Papa never got the chance to take with his own father, the whole crew is packed and ready for a cross-country adventure. Things get off to a rocky start when the car breaks down on their way to pick up Papa. But they really veer off course when Laney discovers that Jessie and Orlando are interviewing at a college once they get to California. How can they even think about leaving New York? Wouldn't that change their family? And how can she and her other siblings stop them? Exploring themes of leaving home, embracing change, and the lessons to be learned when we go to a new place, The Vanderbeekers on the Road is every bit a journey.